2020
DOI: 10.3390/polym12071434
|View full text |Cite
|
Sign up to set email alerts
|

Reliable Characterization of Organic & Pharmaceutical Compounds with High Resolution Monochromated EEL Spectroscopy

Abstract: Organic and biological compounds (especially those related to the pharmaceutical industry) have always been of great interest for researchers due to their importance for the development of new drugs to diagnose, cure, treat or prevent disease. As many new API (active pharmaceutical ingredients) and their polymorphs are in nanocrystalline or in amorphous form blended with amorphous polymeric matrix (known as amorphous solid dispersion—ASD), their structural identification and characterization at nm scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Recent studies have also reported about damage-free LL EELS signatures of organic specimens , but none of them provides maps of the signals. Conversely, other authors used higher electron doses to map the signal of MOF glass blends, probably inducing beam damages.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have also reported about damage-free LL EELS signatures of organic specimens , but none of them provides maps of the signals. Conversely, other authors used higher electron doses to map the signal of MOF glass blends, probably inducing beam damages.…”
Section: Resultsmentioning
confidence: 99%
“…However, studying organic and organic–inorganic nanomaterials remains a delicate task, as they are extremely sensitive to radiation damage. Beam-induced radiolysis and knock-on may result in structural (shrinking, amorphization) and chemical damages (loss of mass and bond breakage), affecting the nanomaterial’s integrity. Noticeably, by employing damage preventive conditions (cryo-holder, low-dose or aloof configuration), recent works have shown the powerful possibilities offered by EELS for analyzing organic molecules, polymers, MOFs, and MOF glass composites in the energy ranges corresponding to IR, UV, and X-rays. , But, to date, none of them has coupled the analysis in the three energy windows. Yet, exploiting the entire energy range would provide a signal complementarity allowing an in-depth characterization of the nanomaterial composition but also monitoring reactional mechanisms.…”
mentioning
confidence: 99%
“…It is an optical spectrum [ 32 ] used to get Plasmon energy. EELS is applied to identify [ 33 ] the different (organic) compounds used in biological systems or pharmaceuticals and to detect any impurities present [ 34 ] even during the synthesis or formulation process [ 35 ]. Also, EELS is used as a technique for quantification of penetration to cell walls [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Today, this hurdle restricts natural scientist to switch to better-suited algorithms. Instead it pushes them to use algorithms, such as the 'Richardson-Lucy-Algorithm'(RLA), Fourier-ratio deconvolution or Wiener filtering [25][26][27][28][29][30][31], that cannot compete with modern algorithms, such as the ADMM, in terms of adaptability and versatility. By balancing primal and dual residuals, arising from optimality conditions for the ADMM, the penalty parameters can be found adaptively in a stable scheme for image denoising or deconvolution, speeding up convergence and making the algorithm independent on the initial choice of these parameters.…”
Section: Introductionmentioning
confidence: 99%